2008
DOI: 10.1002/art.23886
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α drives cadherin 11 expression in rheumatoid inflammation

Abstract: Objective. Cadherin 11 expressed on fibroblastlike synoviocytes (FLS) plays a key role in normal synovial architecture. The purpose of this study was to examine the expression of cadherin 11 in human synovitis.Methods. Cadherin 11 expression in synovial biopsy samples from patients with various types of arthritis and in lung biopsy samples from patients with interstitial pneumonitis (IP) was examined by immunostaining. The regulation of cadherin 11 expression in human FLS was assessed by quantitative reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 59 publications
2
44
0
4
Order By: Relevance
“…Furthermore, a recent study showed that TNF-α increased cad-11 expression on synovial fibroblasts in vitro and found that the expression level of cad-11 may be higher in inflammatory compared with normal synovium in vivo (39), which may further contribute the synergistic effects of cad-11 with TNF-α on IL-6 production in patients. In addition to increased expression of cad-11 on synovial fibroblasts, activation of JNK was increased when cells were stimulated with cad-11 in the presence of TNF-α (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study showed that TNF-α increased cad-11 expression on synovial fibroblasts in vitro and found that the expression level of cad-11 may be higher in inflammatory compared with normal synovium in vivo (39), which may further contribute the synergistic effects of cad-11 with TNF-α on IL-6 production in patients. In addition to increased expression of cad-11 on synovial fibroblasts, activation of JNK was increased when cells were stimulated with cad-11 in the presence of TNF-α (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because cad-11 has also been reported to be up-regulated on fibroblasts in other inflamed tissues such as skin (49) and lung (39), it is likely that cad-11 plays a similar role in fibroblastmediated inflammation in these and other tissues as well.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest in this context is the fact that IL-1␣ A final important issue is how the distinct inflammatory milieu in the inflamed SpA joint translates into differences in phenotype and disease progression as compared with that in the inflamed RA joint. In RA, TNF␣ and IL-1␤ are important drivers of bone and cartilage damage (46)(47)(48)(49)(50). Although lower levels of these cytokines in the inflamed SpA joint may contribute to the preservation of tissue integrity, no clear differences in downstream destructive processes have yet been demonstrated between SpA and RA (34,46,51).…”
Section: Discussionmentioning
confidence: 99%
“…In RA, TNF␣ and IL-1␤ are important drivers of bone and cartilage damage (46)(47)(48)(49)(50). Although lower levels of these cytokines in the inflamed SpA joint may contribute to the preservation of tissue integrity, no clear differences in downstream destructive processes have yet been demonstrated between SpA and RA (34,46,51). Alternatively, rather than protecting from tissue destruction, low levels of M1-derived cytokines in SpA may contribute by allowing tissue repair (50,52).…”
Section: Discussionmentioning
confidence: 99%
“…It should be pointed out that generation of FLC from RA bone marrow CD34+ cells or pDC was correlated with MMP-1 levels in culture supernatants (Hirohata et al,2001;Hirohata et al,2011). On the other hand, it has been demonstrated that cadherin-11 is abundantly expressed in type B synoviocytes (Chang et al,2010) compared with lung or dermal fibroblasts (Vandooren et al,2008). Accordingly, the FLC induced from RA and OA bone marrow pDC expressed comparable amounts of cadherin-11 mRNA to RA and OA synovial FLC (Hirohata et al,2011).…”
Section: Capacity Of Bone Marrow DC To Differentiate Into Type B Synomentioning
confidence: 99%